2017
DOI: 10.1007/s11419-017-0384-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of mepirapim and acetyl fentanyl in authentic human whole blood and urine samples by GC–MS/MS and LC–MS/MS

Abstract: PurposeWe encountered a curious case in which two male subjects self-administered mepirapim plus acetyl fentanyl by different routes, i.e., intravenously and by inhalation. We have thus established a detailed procedure for quantification of mepirapim and acetyl fentanyl in whole blood and urine specimens using gas chromatography (GC)–tandem mass spectrometry (MS/MS).MethodsThe GC–MS/MS method was validated for linearity, extraction recovery, accuracy, and precision. Liquid chromatography–MS/MS was also used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 18 publications
1
15
1
Order By: Relevance
“…The concentrations of mepirapim (554-587 ng/ mL) and acetyl fentanyl (170-212 ng/mL) in blood samples were similar to those of our previous study using the usual IS calibration method (mepirapim, 563-593 ng/mL and acetyl fentanyl, 125-155 ng/mL) [4]. As described in our previous report, the concentrations of mepirapim in blood specimens were much higher than those of various other synthetic cannabinoids (0.1-199 ng/mL) in previous reports of poisoning deaths [2,[18][19][20].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…The concentrations of mepirapim (554-587 ng/ mL) and acetyl fentanyl (170-212 ng/mL) in blood samples were similar to those of our previous study using the usual IS calibration method (mepirapim, 563-593 ng/mL and acetyl fentanyl, 125-155 ng/mL) [4]. As described in our previous report, the concentrations of mepirapim in blood specimens were much higher than those of various other synthetic cannabinoids (0.1-199 ng/mL) in previous reports of poisoning deaths [2,[18][19][20].…”
Section: Discussionsupporting
confidence: 85%
“…The urinary level of unchanged mepirapim in the deceased individual was also as high as 309 ng/mL, although the concentration was slightly lower than that previously found (527 ng/mL) [4]. In addition, our previous study showed that the urine concentration of unchanged mepirapim in a surviving individual was much higher than expected (4900 ng/mL) [4]. Such a high concentration has never been observed for other synthetic cannabinoids; the levels of unchanged synthetic cannabinoids in human urine specimens are generally very low at subnanograms/mL [21].…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations